Problematic behaviours of primary school students during physical education classes - Ostrowska, Małgorzata (Physical education, sport and olympism from a pedagogical perspective, 2023)
The article is an attempt to identify and establish relationships and dependencies between the organisational culture of a primary school and the attitudes of students. The aim of this research is to show the problematic behaviours of students during physical education classes and pedagogical analysis of ambiguous situations due to the lack of a rational approach to the issue of the desired organisational models of the didactic and educational process. The empirical material was a research group consisting of 101 primary school students forming four training teams. The author recorded the results obtained on the basis of pedagogical retrospection (direct observation method, document analysis method). Reflections (qualitative approach) of involved teachers on the problematic behaviour of children and young people depending on the training conditions were also taken into account. The data recording period is September – November 2019 (fourth grade combined groups – 25 students; sixth grade combined groups – 26 students) and September – early November 2022 (fourth grade combined groups – 24 students, seventh grade combined groups – 26 students pupils). The pedagogical project was aimed at collecting information enabling the answer to the research question posed: Do insufficient spatial conditions favour problematic behaviours of students of a selected primary school? In response to the formulated research question, it was stated that insufficient spatial conditions are conducive to problematic behaviour of students in various forms and intensity.